Quantification of main bcr-abl gene transcripts in CML patients using competitive RT-PCR - Ali Nazemi; Mehrdad Hashemi; Shahrashoub Sharifi; Abolfazl Movafagh (Asian Pacific Journal of Cancer Biology, 2016)
Abstract